KEBERLANJUTAN PENGEMBANGAN LORONG GARDEN DALAM MEWUJUDKAN KAWASAN PERKOTAAN RAMAH LINGKUNGAN (ECO CITY) DI MAKASSAR - Andi Wisneni; Abdullah Abdullah; Annas Boceng (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2020)
The Lorong Garden (aisle farming) program is one of the efforts of Makassar City Government to improve the area of narrow aisles or narrow streets in residential areas to make it more comfortable and healthier (ecological) and productive (economic). The program is expected to be able to improve the quality of the environment, community participation, and the economy of the community. The sustainability of its management is influenced by several integrated components. The study aims to analyze the sustainability of Lorong Garden development in Makassar City. Research in the form of a questionnaire interview survey of 126 respondents of the general public and 25 experts /stakeholders in the city of Makassar. Index analysis and sustainability status were using MDS methods Rap-Longgar-Potensial. The results showed that the multidimensional Lorong Garden Program is less sustainable (index 43.02%). Partially, there were two dimensions in the moderately sustainable category namely the ecological dimension (index 51.84%) and the technology dimension (index 65.09%) and three dimensions less sustainable, namely economy (index 46.15%), social (index 49.81) %) and institutional (index 39.20%). Of the total 37 attributes were analyzed, 17 sensitive attributes affected the sustainability of the Lorong Garden development in Makassar City.